Review of Students perception and Students’ Learning Preferences in Learning English at SDN 1 Sembayat - Ummah, Ma’rifatul (Jetlal, 2017)
Teaching English is not only about giving structure or asking student to memorize some vocabularies. The more important thing is encourage the learners to use English on their daily communication. Because English is a foreign language for students in Indonesia, teacher should provide a suitable environment and support the students to practice their language. In order to create an appropriate learning environment, it is important for the teacher to know the students perception and their learning preference in learning English. The participant of this study is students in the 4th to 6th grade of SDN 1 Sembayat. The data was obtained through a yes-no questionnaire and analyzed descriptively using SPSS. The result of this study suggest the teacher to implement an activity based teaching-learning techniques such as TPR, games, and project in order to make an effective language teaching.